Post-Marketing Surveillance of Silodosin in Patients with Benign Prostatic Hyperplasia and Poor Response to Existing Alpha-1 Blockers: The SPLASH Study - Hiroshi Takahashi; Shinichi Kubono; Takehiko Taneyama; Kiyotoshi Kuramoto; Hideki Mizutani; Noriko Tanaka; Masaki Yoshida (Adis, Springer Healthcare, 2019)
Abstract Objectives Our objective was to investigate the effectiveness and safety of silodosin in patients with benign prostatic hyperplasia (BPH) who switched to silodosin from another α1 blocker because of inadequate response. Methods This was a prospective observational study conducted at 715 medical facilities in Japan in patients with BPH who received an α1 blocker other than silodosin for at least 3 months but had experienced unsatisfactory treatment outcomes. Patients completed questionnaires, including the International Prostate Symptom Score (IPSS), quality of life (QOL) score and Overactive Bladder Symptom Score (OABSS) at baseline (time of switching) and after 3 months of treatment with silodosin. Results Overall, 3355 patients were assessed for safety and 3144 patients for effectiveness. Mean ± standard deviation age was 73.1 ± 8.2 years, and most patients had been receiving tamsulosin (53.6%) or naftopidil (45.5%) before silodosin. Silodosin was well tolerated, with an overall incidence of adverse drug reactions of 8.1% and no unexpected safety signals. Significant improvements were observed after switching to silodosin in all effectiveness outcome measures, including total IPSS, all IPSS subscale scores, QOL score, total OABSS, all OABSS subscale scores and residual urine volume. Significant improvements in total IPSS were seen in patients who had been receiving tamsulosin or naftopidil before switching and in almost all other patient subgroups, with the exception of patients with mild symptoms (total IPSS ≤ 7) at baseline. Conclusions This post-marketing analysis indicates that switching to silodosin from tamsulosin or naftopidil significantly improved symptoms associated with BPH, and silodosin was well tolerated in Japanese patients.